2017
DOI: 10.1002/eat.22714
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions in adolescents with binge‐eating disorder and obesity

Abstract: Overall, our results indicate that adolescent BED is associated with only a few alterations in general EF, specifically inhibitory control, and underline BED and educational level as confounding factors in neuropsychological research on obesity. To further delineate EF profiles of adolescents with BED, future research should focus on EF in response to disorder-related stimuli and experimental settings with high ecological validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 51 publications
10
60
1
Order By: Relevance
“…However, our findings are at odds with previous reports of impaired inhibitory control in adults with loss of control over eating (Balodis et al, 2013;Manasse et al, 2016) and in a clinical sample of adolescents with binge eating disorder (Kittel et al, 2017). There are several possible explanations for these contrasting results.…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 99%
See 2 more Smart Citations
“…However, our findings are at odds with previous reports of impaired inhibitory control in adults with loss of control over eating (Balodis et al, 2013;Manasse et al, 2016) and in a clinical sample of adolescents with binge eating disorder (Kittel et al, 2017). There are several possible explanations for these contrasting results.…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 99%
“…First, the handful of studies conducted to date recruited very different samples. Balodis et al (2013) and Manasse et al (2016) used an adult community sample, whereas Kittel et al (2017) used a clinical adolescent sample, and the current study used an adolescent community sample. Selfregulation, and in particular inhibitory control, are generally fully developed by adulthood, with a maturation peak visible during adolescence (Crone, 2009).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 91%
See 1 more Smart Citation
“…Individuals with BED show an increased approach impulse towards reward (Schag, et al, 2013a;Schmidt, Luthold, Kittel, Tetzlaff, & Hilbert, 2016) as well as inhibitory control deficits (Balodis, Grilo, & Potenza, 2015;Hege et al, 2014;Mole et al, 2015;Schag, Sch€ onleber, Teufel, Zipfel, & Giel, 2013b;Schag, et al, 2013a;Svaldi et al, 2014). In a recent study, obese adolescents with BED showed increased general inhibitory control deficits compared with a normal weight control group (Kittel, Schmidt, & Hilbert, 2017). Schag et al (2013a) investigated inhibitory control with eye tracking (ET) methodology in BED without manipulating mood and found general as well as food specific inhibitory control deficits in individuals with BED compared with individuals without BED.…”
Section: Introductionmentioning
confidence: 99%
“…Current research focuses on the neurocognitive profile underlying eating and feeding disturbances. For adolescent binge-eating disorder, previous evidence documented a biased processing of visual food stimuli [12] and impaired inhibitory control [13], likely contributing to binge-eating episode occurrence. In 9-16-year-old youth with loss of control eating, Biehl et al [14] investigated the processing of distracting visual food stimuli during a Go/NoGo task via electroencephalography and found that in NoGo trials, mean P3 amplitudes were significantly higher when the distractor was a high-calorie food stimulus versus a neutral stimulus, while in Go trials, the loss of control group's mean P3 amplitudes did not vary across distractor categories.…”
Section: Clinical Presentation Development Course and Maintenance mentioning
confidence: 99%